SIKAP TOLERANSI BERAGAMA PERSPEKTIF SURAH AL-KAFIRUN MAHASISWA DI KOTA LANGSA - Danil Putra Arisandy; Rabiah Muhammad Nasir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2022)
This study aims to describe the attitude of religious tolerance of students in the city of Langsa from the perspective of surah al-kafirun, to see how tolerance is formed between students of different religious beliefs. In this study using descriptive qualitative research methods. The technique of collecting data is by direct observation and interviews with students studying in the city of Langsa, the city of Langsa itself is one of the cities in Aceh which has a very strong Islamic nuance. The results of this study show that the friendship relationship between Muslim and non-Muslim students is very flexible, the treatment of students in establishing friendships regardless of differences, maintaining harmony, mutual respect and helping each other. Differences in religion are not a dividing wall in a relationship between students, building an attitude of tolerance in a relationship is very necessary, so that a relationship can run well and harmoniously. Muslims are also ordered not to interfere with or follow other religions as contained in the Qur'an Surah Al-Kafirun.